2019
DOI: 10.1111/1556-4029.14056
|View full text |Cite
|
Sign up to set email alerts
|

Psychostimulant Use and Fatal Stroke in Young Adults

Abstract: Psychostimulant use is associated with increased stroke risk. To determine the proportion of psychostimulant users among fatal strokes in young adults (15–44 years), all cases were retrieved from the National Coronial Information System (1/1/2009–31/12/2016). A total of 279 cases were identified: hemorrhagic (259), ischemic (8), thrombotic (8), and mycotic (4). Fifty (17.9%) were identified as psychostimulant users. Psychostimulants in blood were detected in 37/45 where toxicology was available, predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 37 publications
3
28
0
1
Order By: Relevance
“…Substance use disorders (SUD) may be a direct or indirect risk factor for stroke [1-7]. The relationship between illicit drugs and stroke incidence, especially in young adults, has been reported in several studies [1, 2, 8]. However, little is known regarding long-term stroke outcome in substance users.…”
Section: Introductionmentioning
confidence: 99%
“…Substance use disorders (SUD) may be a direct or indirect risk factor for stroke [1-7]. The relationship between illicit drugs and stroke incidence, especially in young adults, has been reported in several studies [1, 2, 8]. However, little is known regarding long-term stroke outcome in substance users.…”
Section: Introductionmentioning
confidence: 99%
“…11 An Australian nation-wide study found that one in five fatal strokes among those aged 15-44 involved psychostimulants, of which methamphetamine was the most common substance implicated. 12 However, incidence of moyamoya vasculopathy in patients with psychostimulant use is unknown due to a lack of sufficient data. 11 To our knowledge, only one case has ever been reported of moyamoya vasculopathy being found in a patient presenting with poly-drug overdose.…”
Section: Open Accessmentioning
confidence: 99%
“…Hypertension associated with psychostimulant use can be either transient or permanent, and in the setting of a hypertensive crisis or sudden blood pressure spike can result in haemorrhagic and, less commonly, ischaemic strokes, subarachnoid haemorrhage , possibly cerebral vasculitis and seizures .…”
Section: Acute Conditionsmentioning
confidence: 99%
“…Persistent systemic hypertension, irrespective of cause, is a potent predisposing factor for stroke, especially where haemorrhagic in nature, and more than 60% of all ischaemic and haemorrhagic stroke patients present to the emergency department with an elevated blood pressure . It is therefore not surprising that psychostimulant users have a higher rate of stroke and that the majority of the strokes identified in an autopsy series were haemorrhagic in nature . In that series, methamphetamine found in 84% of cases and cocaine in 8% were the most commonly used psychostimulants, although other psychostimulants identified on toxicological testing included MDMA in 6%, dimethylamylamine (DMAA) in 4% and phentermine in 2%.…”
Section: Chronic Conditionsmentioning
confidence: 99%